Imposition Of A Copyright Levy In Nigeria: Legal Justifications And Comparative Analysis - Olubiyi, Ifeoluwa A. (Journal of Sustainable Development Law and Policy, 2025)
Copyright owners have the exclusive right to control the reproduction of their works. Since the advent of recording and copying technology, reproducing copyright works has become easier. Cases such as Sony Corp of America v. University City Studios, Inc indicate that copyright owners cannot stop technological advancements since they have both infringing and non-infringing uses. The reality is that private copying/reproduction is damaging to the right of owners and the entire copyright industry. One of the ways this situation is addressed is the imposition of copyright/private copying levies in some jurisdictions. Different rationales have been advanced for the imposition of this levy such as harm/compensation rationale and the statutory licence rationale. Nigeria is joining other jurisdictions in imposing this levy as the Copyright Levy Order 2012 was recently signed into law. This paper discusses the origin and justifications for the imposition of copyright levies. This practice is examined particularly in the light of the ‘fair dealing for private use’ exception under the Nigerian copyright law and in other jurisdictions such as the European Union, Germany, United Kingdom and the United States. It provides a detailed understanding of ‘fair dealing for private use’ and also a justification for the Nigerian Copyright Levy Order under the Nigerian legal system.